2015
DOI: 10.1159/000371895
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Active Surveillance in Low-Risk Prostate Cancer?

Abstract: Background: Active surveillance (AS) represents an expectant treatment strategy for clinically localized prostate cancer (PCa) with low-risk features. Objective: The actual management as well as the pros and cons of AS were evaluated. Methods: A systematic review of the recent literature was performed using the Medline databases. Conclusions: Since a substantial number of men die with rather than from PCa, there is a considerable role for AS in carefully selected men. AS may also represent a strategy to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…3-6). Indeed, it has been shown that clinically localized PCA with low-risk features is best managed by AS (17, 18). However, accurate clinical stratification at diagnosis represents one of the most critical features of this strategy because of the high risk of disease reclassification, which involves 1 out of 3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…3-6). Indeed, it has been shown that clinically localized PCA with low-risk features is best managed by AS (17, 18). However, accurate clinical stratification at diagnosis represents one of the most critical features of this strategy because of the high risk of disease reclassification, which involves 1 out of 3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive literature reviews have shown that clinically localized PCA with low-risk features is best managed by AS, which is an active expectant treatment strategy [13,14] . However, inaccurate clinical stratification at diagnosis represents one of the most challenging features of this treatment strategy because of the high risk of disease reclassification, which involves 1 out of 3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…So far, AS may represent a strategy to reduce the burden of overtreatment due to intensified prostatespecific antigen (PSA) testing [5] . However, in AS protocols, inclusion criteria and appropriate methods for monitoring patients have not yet been standardized because of the evolving knowledge about PCA [6][7][8][9][10][11][12] .…”
Section: Clinical Factors Of Disease Reclassification or Progression mentioning
confidence: 99%